Pengaruh Kualitas Corporate Governance terhadap kinerja Perbankan Syariah: Studi Negara Asia Tenggara - Setyawan, Aris; Mukhlishin, Murniati; Eko Pramono, Sigid (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study aims to examine the effect of corporate governance quality on financial performance in Islamic banking in the Southeast Asian region by looking at the relationship between variables with each other. The dependent variable in this study is Financial Performance proxied by ROA (Return on Asset). The independent variable is Corporate Governance which is proxied by the Size of the Audit Committee, and the Number of Audit Committee Meetings, the Size of the Sharia Supervisory Board, and the Number of Sharia Supervisory Board Meetings. The data analysis method in this study uses multiple linear regression. The research samples used in this study were 10 (ten) Islamic commercial banks in Southeast Asian countries. The data used in this study are secondary data from annual reports and good corporate governance reports of Islamic banking in Southeast Asia for the period 2015-2019. The research findings show that GCG proxied by the Size of the Audit Committee and the Number of Audit Committee Meetings has no significant effect on financial performance proxied by ROA (Return on Asset). Meanwhile, GCG proxied by the Size of the Sharia Supervisory Board and the Number of Sharia Supervisory Board Meetings has a significant effect on financial performance proxied by ROA (Return on Asset). This shows that the role of the Sharia Supervisory Board in ensuring that company operations run in accordance with Islamic values has a very important role and is the core of the integrity and credibility of Islamic Banks and has a significant influence in improving the company's financial performance.